Solution self-assembly of ABC triblock terpolymers with a central crystallizable poly(ferrocenyldimethylsilane) core-forming segment. Issue 20 (24th April 2019) - Oliver, Alex M.; Spontak, Richard J.; Manners, Ian
Abstract : The synthesis and solution self-assembly behavior of a range of linear ABC triblock terpolymers with a central crystallizable poly(ferrocenyldimethylsilane) core-forming segment have been explored. Abstract : The synthesis and solution self-assembly behavior of a range of linear ABC triblock terpolymers (triBCPs) with a central crystallizable poly(ferrocenyldimethylsilane) (PFDMS) core-forming segment have been explored. Two different PIP- b -PFDMS- b -PMMA triBCPs (1 and2 ) (PIP = polyisoprene, PMMA = poly(methyl methacrylate) with different block ratios (1 : 6.2 : 1.0 : 7.6;2 : 1.2 : 1.0 : 1.9) were investigated. TriBCP1 was shown to form either cylinders or a mixed morphology of spheres and cylinders in various selective solvents, whereas triBCP2 yielded either network structures or platelets. The PFDMS core-forming block of the spheres of1 and network micelles of2 formed in hexanes appeared to undergo slow crystallization, leading to the slow transformation to form cylinders and platelets, respectively. The self-assembly behaviour of a PS- b -PFDMS- b -PMVS triBCP (3, block ratio: 7.9 : 1.0 : 5.7; PS = polystyrene, PMVS = poly(methylvinylsiloxane)) was also examined in various solvents and yielded spheres and/or cylindrical micelles showing behavior reminiscent of1 . Despite their disparate self-assembly behavior, seeded growth "living crystallization-driven self-assembly" methods were successfully developed for1–3 using short cylinders of PFDMS diBCPs as initiators to generate cylindrical B–A–B block co-micelles with controlled lengths. Moreover, a "patchy" coronal structure for the B segments was revealed by TEM and AFM analysis of dried samples.